The relationship between salary, benefits and career development with employee satisfaction in Giatmara Kedah - Azizul Hakim, Azizan (2019)
Employee satisfaction is the main factor of any turnover rate in any organization. With satisfied employees, it will be more easier to achieve organization goals or target. This research is to investigate factors of employee satisfaction for trainers of GIATMARA Kedah. The main purpose of the study is to prove the relationship between salary, benefits and career development with employee satisfaction. The study used quantitative method. The population of the study is the trainers of GIATMARA Kedah. The data collected through self-administered questionnaires from 90 trainers of GIATMARA Kedah selected by computerized random selection technique. The questionnaires were adapted from past researchers and the results showed positive relationship between salary, benefits and career development with employee satisfaction. The findings revealed that the trainers of GIATMARA Kedah are satisfied with their work in GIATMARA. This research provides better understanding on the employee satisfaction in GIATMARA Kedah and potential use of findings can b used by the organization as a reference for future research.